2009
DOI: 10.1177/1074248409338929
|View full text |Cite
|
Sign up to set email alerts
|

Dose-Related Shortening of Ventricular Tachycardia Cycle Length After Administration of the KATP Channel Opener Bimakalim in a 4-Day-Old Chronic Infarct Anesthetized Pig Model

Abstract: Potassium channel openers are known to act on potassium ATP-dependent channels in cardiac tissue. Such agents may exacerbate acceleration of acute ischemia-induced ventricular repolarization and aggravate arrhythmias. To test whether activation of K( ATP) channels during the healing period of myocardial infarction (MI) can still influence the electrophysiologic properties and the type of inducible arrhythmias, we investigated the effects of bimakalim (BIM) on sustained ventricular tachycardia (VT) 4 days after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…[3][4][5] To address these limitations we hypothesized that QT/QRS might serve as a readily measurable local estimate of cardiac wavelength and called this parameter the "index of cardio-electrophysiological balance." [3][4][5] To address these limitations we hypothesized that QT/QRS might serve as a readily measurable local estimate of cardiac wavelength and called this parameter the "index of cardio-electrophysiological balance."…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[3][4][5] To address these limitations we hypothesized that QT/QRS might serve as a readily measurable local estimate of cardiac wavelength and called this parameter the "index of cardio-electrophysiological balance." [3][4][5] To address these limitations we hypothesized that QT/QRS might serve as a readily measurable local estimate of cardiac wavelength and called this parameter the "index of cardio-electrophysiological balance."…”
Section: Discussionmentioning
confidence: 99%
“…Only limited in vitro data are available on cardiac wavelength as a risk stratifier, mainly due to the invasive nature to measure it. [3][4][5] To address these limitations we hypothesized that QT/QRS might serve as a readily measurable local estimate of cardiac wavelength and called this parameter the "index of cardio-electrophysiological balance." It is generally accepted that QRS duration in the absence of a clear bundle branch block is inversely proportional to conduction velocity in the cardiac ventricle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This difference in duration reflects increased heterogeneity of repolarization, another electrophysiological substrate predisposing to arrhythmia. Finally it has been suggested that changes in cardiac wavelength λ [λ = effective refractory period (ERP) × conduction velocity (CV)] promote reentrant arrhythmias (Aidonidis et al, 2009). Since changes in APDs reflect the changes in ERP, therefore, agents that prolong APDs tend to increase the risk for torsades de pointes while agents that shorten APDs tend to increase the risk for ventricular fibrillation (Hondeghem, 2008;Hondeghem, Dujardin, Hoffmann, Dumotier, & De clerk, 2011).…”
Section: Electrical Remodeling Of the Ventriclementioning
confidence: 99%
“…In addition, increased oxidation directly activates SarcKATP (sarcolemmal-ATPdependent potassium) channels (Tokube et al, 1996(Tokube et al, , 1998 and changes the inactivation kinetics of L-type calcium channels (Belevych et al, 2009). SarcKATP channels opening reduces the action potential duration and effective refractory period (Aidonidis et al, 2009;Ferrier & Howlett, 2005) which in turn increases the incidence of cardiac arrhythmia (Billman, 2008;Billman et al, 2004). There is credible evidence that during reperfusion, production of oxygen free radicals increase in ischemic tissue (Bolli et al, 1989;Manning et al, 1988) and the use of ROS (reactive oxygen species) scavengers is associated with successful decrease in the reperfusion-induced arrhythmias (Cho et al, 2007;Hicks et al, 2007;Konya et al, 1992).…”
Section: Discussionmentioning
confidence: 99%